A comparative review of policy and practice for education for sustainable development/education for global citizenship (ESD/GC) in teacher education across the four nations of the UK. (July 2016) - Bamber, Philip; Bullivant, Andrea; Glover, Alison; King, Betsy; McCann, Gerard
The early 21st century has seen a period of extreme turbulence in education at all levels in the UK. Although education policy was administrated on a territorial basis before 1999, the 1998–1999 devolution settlement has amplified the complexity of education policy and practice across England, Wales, Scotland and Northern Ireland. Through a comparative review of teacher education across the four nations, this article will highlight aspects of divergence and convergence of policy and practice with a particular focus on education for sustainable development/education for global citizenship (ESD/GC). The implications for ESD/GC will be considered in relation to statutory teaching standards/competencies, values and ideologies, curriculum and pedagogy, and the role of the third sector. This discussion will identify opportunities and challenges facing ESD/GC in teacher education across the four nations.